The causes and consequences of the semantic devaluation of the words пафос and пафосный in modern Russian - Babenko N. (Слово.ру: балтийский акцент, 2014)
This article considers the radical changes in the functioning of literary lexis in the Russian language of the early 21st century, namely the causes and consequences of the semantic devaluation of the noun пафос and its syntactic derivate, the adjective пафосный, whose semantic transformation is explained by the speech expansion of glamorous lifestyle as an aggressive subculture.